Information literacy skills: Hong Kong primary teachers' perceptions of the role of the teacher librarian - Leung, Yuet Ha (2018)
The thesis reviewed the changes to the role of teacher librarians and the implications of this for primary teachers. The study sought to explore the teachers’ views about information literacy skills, who should teach them and the role of the teacher librarian.